2013
DOI: 10.1377/hlthaff.2012.1246
|View full text |Cite
|
Sign up to set email alerts
|

Policy Makers Will Need A Way To Update Bundled Payments That Reflects Highly Skewed Spending Growth Of Various Care Episodes

Abstract: Bundled payment entails paying a single price for all services delivered as part of an episode of care for a specific condition. It is seen as a promising way to slow the growth of health care spending while maintaining or improving the quality of care. To implement bundled payment, policy makers must set base payment rates for episodes of care and update the rates over time to reflect changes in the costs of delivering care and the components of care. Adopting the fee-for-service paradigm of adjusting payment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
0
11
0
1
Order By: Relevance
“…; Rosen et al. ; Roehrig and Rousseau ; Starr, Dominiak, and Aizcorbe ; Aizcorbe and Nestoriak ; Dunn et al. , ; Dunn, Leibman, and Shapiro ).…”
Section: Which Price Index To Apply?unclassified
See 3 more Smart Citations
“…; Rosen et al. ; Roehrig and Rousseau ; Starr, Dominiak, and Aizcorbe ; Aizcorbe and Nestoriak ; Dunn et al. , ; Dunn, Leibman, and Shapiro ).…”
Section: Which Price Index To Apply?unclassified
“…Rosen et al. () found that 10 percent of the conditions account for 82.5 percent of spending growth based on commercial claims data from 2003 to 2007. Large differences in growth rates are also found at the disease‐category level using BEA's HCSA data.…”
Section: Which Price Index To Apply?mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the distribution of spending growth is specific to each condition, a point that has been highlighted previously. 16 There is a wide degree of heterogeneity in spending growth across conditions and in the likely factors driving their growth. For example, exhibit 3 shows that per capita spending for hepatitis is driven by rising treatment costs rather than by growth in prevalence.…”
Section: Discussionmentioning
confidence: 99%